STRATEGI DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN KEPULAUAN MERANTI DALAM MENGKOMUNIKASIKAN GERAKAN REHABILITASI HUTAN DAN LAH MANGROVE - Wahyu Dicka Permata; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Damaged forests can cause disasters such as floods and landslides. This also happens in one region of Indonesia, Meranti Islands district have also suffered damage from natural disasters or human activity itself, forest destruction worst that happened in the district of Meranti namely mangrove forests, where the destruction of mangrove forests could impact beach abrasion. The purpose of this study was to determine how the Department of Forestry and Plantation Meranti Islands regency in running communication strategy in the program implementation mangrove forest and land rehabilitation.In this study the authors used a qualitative research method with a phenomenological approach. Data collection techniques are grouped through observation, interviews and documentation. The informant in this research were six people who were taken by purposive sampling techniques, ie 5 civil servants and 1 community. Interactive data analysis type the researchers use to describe the results of research into techniques for data analysis and data validity checking researcher using triangulation techniques.The results in which the communication strategy is executed in accordance with the steps of planning strategies, ie; to identify their communication, communication media selection and assessment destination of the message. From interviews and observations of researchers got field indicates that the Department of Forestry and Plantation Regency Meranti has been doing business in recognizing the target of communication, working with some of the media, both print and electronic media as well as services to create and examine the messages to be conveyed to the public related program mangrove forest and land rehabilitation.Keyword: Communication strategy, Foresty and Plantation Service Meranti Island, Mangrove.